RATIONAL MANLINESS AS GOODNESS: RESPONSES TO INTERSECTIONAL DOMINATION AND THE PRESERVATION OF THE MORAL SELF IN HIGHER EDUCATION - Beckles-Raymond, Gabriella (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2021)
How should we understand the persistence of racism in the British academy and the efficacy of current responses to address racism? Drawing on philosophers Sylvia Wynter and Charles Taylor, I claim higher education in Britain is a manifestation of ‘Rational Manliness’ – a co-constitutive moral framework - as a hypergood. I then, deploy the Rational Manliness framework to evaluate three common responses to injustice in higher education – Rational Man fragility, confessions/self-forgiveness, and intellectual decolonization. Ultimately, I argue that, insofar as higher education holds Rational Manliness as a hypergood, responses to injustice are rooted in a commitment to preserve a sense of self as good, by maintaining the intersectional matrix of domination. As such, I suggest that higher education in Britain must be reconstituted and transformed in ways that depart from Rational Manliness as a hypergood towards establishing the-eradication-all-forms-of-domination as a morally defensible hypergood.